Orientation Characteristics of Sasak Traditional House (Bale Tani) in Limbungan Hamlet, East Lombok Regency - Dendi Sigit Wahyudi; Antariksa Antariksa; Sri Utami (Journal of Social Science, 2022)
Traditional settlements are very synonymous with the customs and cultural traditions of the people in each region. Traditional settlements essentially and generally have rules for the pattern and arrangement of houses in settlements that follow the rules of local culture and existing traditions, one of which is in terms of orientation in home settlements. The pattern of the house's orientation is also found in the settlements in Limbungan Hamlet, but the orientation of the Sasak tribe in this village has a very diverse characteristic. Limbungan hamlet is a settlement located on contoured soil conditions and in a very high hilly area. The settlement pattern in this hamlet is generally symmetrical, forming settlement groups that follow the contours of the settlement. The purpose of this research is to be able to know and be able to explain the characteristics of the orientation of the traditional house of the Sasak tribe (bale tani) in the Limbungan hamlet, which has a traditional house orientation direction based on the approach of customary rules and traditions of the indigenous people or local communities. The research methodology used is a descriptive analysis qualitative method approach by conducting a comparative analysis technique on the traditional settlement group of the Sasak Tribe. The results of research on these settlements can show that there is a basis that the emergence of the orientation of the Sasak tribe is related to the concept of house orientation facing east. The house's orientation is good, namely the direction facing east and west, and strongly against the direction facing south and north. The east direction of the traditional house considers the topographical conditions of the placement of the house. Houses in hilly topography will generally always be oriented towards the high ground and face east, especially Limbungan is always at the foot of Mount Rinjani